WHO takes action to promote the health of refugees and migrants - Gostin, Lawrence O; Abubakar, Ibrahim; Guerra, Ranieri; Rashid, Sabina F; Friedman, Eric A; Jakab, Zsuzsanna (Elsevier, 2022)
This article was published in The Lancet, Elsevier [© 2019 Elsevier Ltd. All rights reserved.] and the definite version is available at: https://doi.org/10.1016/S0140-6736(19)31051-7 The Journal's website is at: https://www.thelancet.com/journals/lancet/article/PIIS0140-6736(19)31051-7/fulltext